Pengaruh Inklusi Keuangan, Fintech, Modal Sendiri dan Modal Manusia Terhadap Kinerja UMKM - Zalayeta, Nailus Zahrani; Aisa, Nabila Na'ma (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
MSMEs have a major role in the Indonesian economy, but still face challenges such as access to finance, capital, and technology. This study aims to examine the influence of financial inclusion, financial technology, own capital, and human capital on the performance of MSMEs in Rejowinangun Village. Using quantitative methods and multiple linear regression tests, this study involved 60 respondents of MSME players as samples. The results revealed that only financial technology has a positive and significant effect on MSME performance. The other variables have no significant effect. This research is useful in encouraging the adoption of financial technology by MSMEs to improve performance and competitiveness. In addition, the results can serve as a reference for the government and policy makers in designing more effective digitization and funding access programs. Therefore, support for digitalization and access to funding for MSMEs needs to be continuously improved. This research also opens up opportunities for future studies to explore other aspects that affect MSME performance more comprehensively.